Editorial for the Genetics of Alzheimer’s Disease Special Issue: October 2021 - Ibanez, Laura; Miller, Justin B. (Genes, 2021)
Alzheimer’s disease is a complex and multifactorial condition regulated by both genetics and lifestyle, which ultimately results in the accumulation of β-amyloid (Aβ) and tau proteins in the brain, loss of gray matter, and neuronal death [...]